Learners Need Analysis of English for Specific Purpose of Culinary Art Focus on Servant of Restaurant in Vocational School - kusumaningsih, dwi; Stevanus, Felicity Bte; Oro, Skolastika Nina; Kelen, Frederikus; Surwanti, Dita ((JELE) Journal Of English Language and Education, 2020)
Need analysis is an important thing to identify student’s needs based on their field. The purpose of this study, the researcher wants to know the course about servant in the restaurant so the researchers know about students’ need in culinary art. The researchers get the data from three restaurants that are: Aglioo Resto; K’meals, Food, Beer and Music Resto; and Bilik Kayu Resto to know what the needs of being a servant especially the language that servant used to communicate with customer. The researchers also get the data from SMK 2 Bopkri Yogyakarta. The method that the researchers used in this research was qualitative with interview and questionnaire to collecting the data. The result of this study is SMK 2 Bopkri Yogyakarta use English for specific purposes. The students in servant program must be able to communicate with customer by using foreign language especially English language. They should  understand the menu, cooking utensils, types of services such as American service, and product of non-alcohol drinks. The students should master all skills.  The students also should understand how servant greeting the customers, receiving customers, sitting the customers, billing, and until farewell. In restaurants, the servant should master English language to communicate with foreign customers. They not only know about menu but they have to know about good view in that country. After compare the data from the school  and the restaurants, the material which is taught by the english teacher in servant program is appropriate with servants’ need.